Pre-Operative Tumor Localization and Evaluation of Extra-Capsular Extension of Prostate Cancer: How Misleading Can It Be? - Kan, Raymond Wai-man; Kan, Chi-fai; Ho, Lap-yin; Chan, Steve Wai-hee (Urology Journal, 2014)
Abstract Purpose: To verify the accuracy of transrectal ultrasound-guided prostatic biopsy (TRUS Bx), magnetic resonance imaging (MRI) and their combination in evaluating the laterality of prostate cancer and to determine the accuracy of MRI in assessing extra-capsular extension of prostate cancer. Materials and Methods: We retrospectively reviewed our past 100 consecutive series of radical prostatectomy performed between February 2010 and April 2012 at our institution. Their TRUS Bx and MRI results were compared with the pathology of the radical prostatectomy specimens. For tumor localization, we calculated the accuracies in unilateral diseases, bilateral diseases, overall accuracies and Cohen Kappa concordance coefficient of TRUS Bx, MRI and their combination. For the assessment of extra-capsular extension, we calculated the sensitivity, specificity, positive predictive value, negative predictive value, overall accuracy, likelihood ratio positive and likelihood ratio negative of MRI. Results: Eighty-two percent of our radical prostatectomy specimens had bilateral tumor involvement and 32% had extra-capsular extension. The accuracies of TRUS Bx in unilateral disease, bilateral disease and overall accuracy were 15.2%, 91.4% and 43.6%, respectively. The accuracies of MRI in unilateral disease, bilateral disease and overall accuracy were 11.1%, 66.7% and 38.9%, respectively. When combining the assessment of TRUS Bx and MRI, the accuracies in unilateral disease, bilateral disease and overall accuracy were 16.7%, 75% and 55.6%, respectively. The Cohen Kappa concordance co-efficient of TRUS Bx, MRI, and combination of them were 0.1165, -0.2047 and -0.1084, respectively. The positive predictive value, negative predictive value, sensitivity, specificity, overall accuracy, likelihood ratio positive and likelihood ratio negative of MRI in assessing extra-capsular extension were 33.3%, 69.8%, 5.9%, 94.9%, 67.9%, 1.16 and 0.99, respectively. Conclusion: TRUS Bx, MRI, and their combination had poor concordance and limited accuracies in assessment of the laterality of tumor involvement. The combination of TRUS Bx and MRI offered a better of accuracy when compared to either modality alone. MRI was a specific, but not sensitive tool in assessing the presence of extra-capsular extension. <!--[if gte mso 9]> Normal 0 0 2 false false false MicrosoftInternetExplorer4 <![endif]--> <!--[endif] -->